Miltefosine enhances infectivity of a miltefosine-resistant Leishmania infantum strain by attenuating its innate immune recognition. - Dimitri Bulté (Public Library of Science (PLoS), 2021)
Background Miltefosine (MIL) is currently the only oral drug available to treat visceral leishmaniasis but its use as first-line monotherapy has been compromised by an increasing treatment failure. Despite the scarce number of resistant clinical isolates, MIL-resistance by mutations in a single aminophospholipid transporter gene can easily be selected in a laboratory environment. These mutations result in a reduced survival in the mammalian host, which can partially be restored by exposure to MIL, suggesting a kind of drug-dependency. Methodology/principal findings To enable a combined study of the infection dynamics and underlying immunological events for differential in vivo survival, firefly luciferase (PpyRE9) / red fluorescent protein (DsRed) double-reporter strains were generated of MIL-resistant (MIL-R) and syngeneic MIL-sensitive (MIL-S) Leishmania infantum. Results in C57Bl/6 and BALB/c mice show that MIL-R parasites induce an increased innate immune response that is characterized by enhanced influx and infection of neutrophils, monocytes and dendritic cells in the liver and elevated serum IFN-γ levels, finally resulting in a less efficient establishment in liver macrophages. The elevated IFN-γ levels were shown to originate from an increased response of hepatic NK and NKT cells to the MIL-R parasites. In addition, we demonstrated that MIL could increase the in vivo fitness of MIL-R parasites by lowering NK and NKT cell activation, leading to a reduced IFN-γ production. Conclusions/significance Differential induction of innate immune responses in the liver was found to underlie the attenuated phenotype of a MIL-R parasite and its peculiar feature of drug-dependency. The impact of MIL on hepatic NK and NKT activation and IFN-γ production following recognition of a MIL-R strain indicates that this mechanism may sustain infections with resistant parasites and contribute to treatment failure.